Chaotic Dynamics of Cage Behavior in a High-Speed Cylindrical Roller Bearing - Long Chen; Xintao Xia; Haotian Zheng; Ming Qiu (Shock and Vibration)
This paper presents a mathematical model to investigate the nonlinear dynamic behavior of cage in high-speed cylindrical bearing. Variations of cage behavior due to varying cage eccentricity and cage guidance gap are observed. Hydrodynamic behavior in cage contacts is taken into consideration for a more realistic calculation of acting forces owing to high working speed. Analysis of real-time cage dynamic behavior on radial plane is carried out using chaos theory based on the theoretical and mathematical model established in the paper. The analytical results of this paper provide a solid foundation for designing and manufacturing of high-speed cylindrical roller bearing.